Dynamic CT Perfusion Imaging with Acetazolamide Challenge for Evaluation of Patients with Unilateral Cerebrovascular Steno-Occlusive Disease - Chen, A.; Shyr, M.-H.; Chen, T.-Y.; Lai, H.-Y.; Lin, C.-C.; Yen, P.-S. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Perfusion CT (PCT) has the ability to measure quantitative values and produce maps of cerebral blood flow (CBF), cerebral blood volume (CBV), and mean transit time (MTT). We assessed cerebral hemodynamics by using these parameters and acetazolamide challenge in patients with cerebrovascular steno-occlusive disease.METHODS: Fifteen patients underwent PCT with acetazolamide challenge. Comparison of mean CBF, CBV, and MTT was determined between hemispheres and before and after acetazolamide challenge. Hemispheric ratio and percent change due to acetazolamide administration were also calculated. Absolute values and percent changes 2 SDs outside the mean from the nonstenotic hemispheres were defined as abnormal.RESULTS: Significant decreases in CBF (−25.1%, P = .003) and significant increases in MTT (47.1%, P < .001) were found in stenotic hemispheres. After acetazolamide challenge, significant changes in CBF (−39.5%, P < .001) and MTT (92.9%, P < .001) were also seen. The acetazolamide test significantly decreased CBF hemispheric ratio (−20.3%, P < .001) and increased MTT hemispheric ratio (30.8%, P = .002), making both maps more asymmetric. Significance in CBF and MTT percent changes (P < .001 and P = .005, respectively) was found between hemispheres. When CBF percent changes were assumed to represent the true determinant of hemodynamic impairment, normal ranges of baseline MTT value and MTT percent changes demonstrated sensitivities of 66.7% and 100% and specificities of 58.3% and 75%, respectively, for detecting patients with hemodynamic impairment.CONCLUSION: Parameters obtained from PCT with acetazolamide are promising for the evaluation of cerebral hemodynamics in patients with cerebrovascular steno-occlusive disease.